Canine vegan biscuits produced with inulin and blackberry flour (Research, Society and Development, 2021)
Pet food accounts for more than 60% of the total sales in the pet market, with emphasis on products with the addition of functional ingredients and health claims. The objective of the present study was to manufacture vegan canine biscuits, as snacks, containing the following functional ingredients: inulin, blackberry flour (BBF), and hydrolyzed soy protein (HSP). Four formulations were made, as follows: CB1, a control formulation, without the addition of inulin, BBF, and HSP. For the other formulations, the amount of BBF and HSP was set at 50 and 35 g/kg, respectively, and the inulin contents were 30, 60, and 90 g/kg, for the formulations CB2, CB3, and CB4, respectively. All biscuits were evaluated for their technological properties. The increase in inulin significantly reduced the hardness of the biscuits from 30 N (CB1) to 20 N (CB3 and CB4). The biscuits with blackberry exhibited a pink color, which shows that this natural ingredient can be used as a food coloring ingredient, thus avoiding the use of synthetic additives. CB3 and CB4 had the same acceptance as CB1, indicating no sensory rejection of the ingredients by the dogs. The BBF increased (p-value